Human landscapes : contributions to a pragmatist anthropology - Dreon, Roberta (Albany : State University of New York Press, 2022)
"Human Landscapes works out a pragmatist anthropology which the Classical Pragmatists never put together in a comprehensive form--despite the many insights on the topic to be found in Dewey's, James's, and Mead's texts. Roberta Dreon retrieves and develops this material in its astonishing modernity concerning current debates on the mind as embodied and enacted, philosophy of the emotions, social theory, and studies about the origins of human language. By assuming a basic continuity between natural developments and human culture, this text highlights the qualitative, pre-personal, habitual features of human experience constituting the background to rational decision-making, normativity, and reflection. The book rests on three pillars: a reconceptualization of sensibility as a function of life, rather than as a primarily cognitive faculty; a focus on habits, understood as pervasive features of human behaviors acquired by attuning to the social environment; and an interpretation of human experience as "enlanguaged," namely as contingently yet irreversibly embedded in a linguistic environment that has important loop effects on human sensibility and habitual conduct."--Provided by publisher.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed on February 13, 2023).
JSTOR
Keywords: Psychology; Philosophy; Pragmatism; Psychology; Philosophy; Psychologie; Philosophie; Pragmatisme; psychology; philosophy; pragmatism; Philosophy; Pragmatism; Psychology